A Gulliver Scaloposaurus (Therapsida, Therocephalia) from the Katberg Formation of South Africa and its implication for Lilliput assemblages during the Early Triassic recovery. (December 2022) - Huttenlocker, Adam K.; Botha, Jennifer; Browning, Claire; Kulik, Zoe; Tshibalanganda, Muofhe; du Plessis, Anton
Abstract: 'Scaloposaurs' represent a wastebasket taxon of small therocephalian therapsids once believed to be close to the evolutionary ancestry of mammals. The group is now thought to be made up of mostly paedomorphic or juvenile therocephalians belonging to various families. Here, a new large therocephalian is described from the Early Triassic Lystrosaurus declivis Assemblage Zone (AZ) on the farm Donald 207 (formerly 'Fairydale') in South Africa's Karoo Basin, an historic fossil locality. The new specimen consists of a mostly articulated skull and anterior postcranial skeleton, but with a slightly crushed rostrum, requiring micro-computed tomography (μCT) to virtually restore the diagnostic palate morphology. Apomorphic features including a bony maxillovomerine bridge, two small maxillary precanines, and at least eight or nine upper postcanines—are consistent with the genus Scaloposaurus . However, linear dimensions of the new specimen (basal skull length 110 mm) greatly exceed others, being 84% larger than the previous largest Scaloposaurus specimen. Our discovery of the largest Scaloposaurus reveals distinctive subadult morphology in the genus and underscores hypothesized plasticity in growth patterns of Permo-Triassic therapsids gleaned from histologic analysis. Nevertheless, mixed-age theriodont assemblages are occasionally documented in the Lystrosaurus declivis AZ, and fully-grown specimens continue to be remarkably rare in the recovery fauna following the Permo-Triassic mass extinction. Importantly, this interval has also been characterized by apparent short-term reductions in body sizes of fossil assemblages (Lilliput phenomena). These findings are consistent with our recent hypothesis that, unlike in preceding time intervals, juvenile excess mortality was relatively high during the Early Triassic extinction recovery. Highlights: We report a large specimen of Scaloposaurus, the first in a record dominated by immature specimens. The new specimen contributes to a revised differential diagnosis. Results support Triassic "Lilliput phenomena" were influenced by interplay of processes.